2022
DOI: 10.1136/annrheumdis-2021-221126
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab in patients with new onset polymyalgia rheumatica (PMR-SPARE): a phase 2/3 randomised controlled trial

Abstract: BackgroundPolymyalgia rheumatica is the second most common inflammatory rheumatic disease of people >50 years. Glucocorticoid therapy is highly effective, but many patients require treatment for several years. Effective glucocorticoid sparing agents are still needed.MethodsIn this double-blind, multi-centre phase 2/3 clinical trial, we randomly assigned 36 patients with new onset polymyalgia rheumatica from three centres to receive subcutaneous tocilizumab (162 mg per week) or placebo for 16 weeks (1:1 rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 31 publications
3
28
0
4
Order By: Relevance
“…We provide genetic evidence to support IL-6Ri as a therapeutic target for reducing PMR risk. These findings support results of the recent PMR-SPARE trial, in which 19 patients with new-onset PMR who were randomised to tocilizumab demonstrated superior rates of glucocorticoid-free remission, compared with 17 given placebo 5. The current results additionally provide insights into the therapeutic potential of IL-6Ri as monotherapy.…”
supporting
confidence: 86%
“…We provide genetic evidence to support IL-6Ri as a therapeutic target for reducing PMR risk. These findings support results of the recent PMR-SPARE trial, in which 19 patients with new-onset PMR who were randomised to tocilizumab demonstrated superior rates of glucocorticoid-free remission, compared with 17 given placebo 5. The current results additionally provide insights into the therapeutic potential of IL-6Ri as monotherapy.…”
supporting
confidence: 86%
“…Three studies were excluded because we did not find data on the statistical significance or the studies did not pass the quality appraisal evaluation. Therefore, we included eight articles in this review [4,[11][12][13][14][15][16][17]. The PRISMA flowchart is illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies applied GC concomitantly with TCZ (GC combination) [11,12,14,15], and three used TCZ as monotherapy [11,14,15]. In addition, Akiyama et al evaluated monotherapy and GC combinations [4], as represented in Table 4.…”
Section: Year Of Publication Country Study Design Total Of Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, IL-6 receptor blocking therapy has shown positive results as GC sparing therapy in GCA ( 10 ). Promising results with this therapy have also been reported in PMR ( 11 , 12 ). However, tocilizumab monotherapy is not recommended for these diseases and combination treatment with GC is still imperative, especially in GCA.…”
Section: Introductionmentioning
confidence: 84%